Issues and Concerns in the Digital Media Eco-System : Regulation in India - Bharthur, Sanjay (Journal of Information and Knowledge, 2023)
Perceptions about Indian media vary and are dependent on where you are located as within the country or part of the Indian diaspora or established media outlets' view quite often described as western media. To Indians, the shrillness of TV news debates and the so-called diverse panellists' perspectives reflects one aspect of how liberal Indian media can be, as well as the tempered variations of the same in the daily newspapers of your choice. Intellectuals are worried and critical about the skewed nature of such debates and their proximity to the ruling polity dispensation. Some express their views or concerns through write-ups in media outlets outside the country. The growth of news media outlets sectoral, as in newspapers, radio, television etc. or converged as in the present digital ecosystem, is imbued within the media's relationship to the formation and sustenance of democratic structures and upheld freedom as an abiding principle. Indian media in the past has always been regarded as relatively accessible when compared to many other developing contexts and is now being debated as the shift from an editorial policy-driven entity to a platform-based content in a free for all user-generated content has occurred not only in India but in other countries as well. The transition from explicit frameworks as laws and ethics to regulating social media platforms is dynamic as well problematic when weighed against conventional notions for freedom of media etc. What, then, are some of the issues and or challenges in the Indian digital ecosystem that will be the focus of this invited article.